Penerapan Arstitektur Neo Vernakular Pada Perancangan Gedung Pertunjukkan Seni Di Kawasan Baki, Solo Baru - Astuti, Elitya Daisy; Sulistiowati, Anggraeni Dyah; Iskandaria, Harfa (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2024)
Performing arts is a forum or organization for performing arts, which consists of movement arts, music and fine arts. Thus, a new building is needed that can support all activities and facilities for cultural arts performances and entertainment performances that are more adequate, so that the cultural heritage of the arts can continue to be channeled optimally. Based on these needs, a building will be created specifically as an arts center in Solo. There are several facilities that will later be able to be used, such as wider parking space allocation, complete international standard facilities, as well as Neo Vernacular Architecture buildings that can reflect the local characteristics of the region. This international standard facility has a more modern setting such as an organized stage, closed building and so on. In line with global trends, in the future the people of Solo will need cultural spaces with a local atmosphere, which are private and specific rather than commercial spaces. Baki, Solo Baru has potentials related to the performing arts, which can support the existence and development of the performance building. The existence of this Performing Arts Building is a place to accommodate all activities related to performing arts